ANALISIS PENERAPAN PROTOKOL KESEHATAN COVID-19 MASA NEW NORMAL DI BANDARA INTERNATIONAL KUALANAMU - Sitompul, Anita Julistika Sari; Utami, Tri Niswati; Fitriani, Arifah Devi (Indonesian Trust Health Journal, 2023)
The corona virus has become an epidemic in several countries. At Kualanamu International Airport, several cases of corona virus were found in several employees at the airport terminal who were in direct contact with several passengers every day in carrying out checks. The reason for the large number of employees being exposed is because there are still workers at the airport and passengers and visitors who do not comply with health protocols, namely not using masks properly and correctly and there are still passengers who do not restrict distance. The COVID-19 case at Kualanamu International Airport was found in employees in June and 9 employees were found to be exposed to COVID-19. The purpose of this study was to determine the implementation of the new normal health protocol at Kualanamu International Airport. This research is descriptive using qualitative research methods conducted at Kualanamu International Airport by using in-depth interviews with 4 AVSEC officers, 3 airlines, 5 passengers, 2 health workers, and 2 restaurant managers. From the results of the research that has been done, it can be seen that the implementation of the new normal COVID-19 health protocol at Kualanamu International Airport is in accordance with the regulations set by the government. The application of the health protocol, several obstacles and causes of non-compliance with the health protocol were found, because there were some passengers and visitors who were negligent in implementing the health protocol not wearing masks properly, such as lowering the mask on the mouth or chin area and passengers who did not restrict distance, especially on during check-in, validate the results of the rapid / swab test as well as when going to or from the plane. For this reason, Kualanamu International Airport Officer is expected to continue to convey the importance of implementing the new normal COVID-19 health protocol. Passengers are also expected to increase discipline in implementing the COVID-19 health protocol. Abstrak Virus corona telah menjadi wabah di beberapa negara. Di Bandara International Kualanamu ditemukan beberapa kasus corona virus pada beberapa karyawan yang berada di terminal bandara yang setiap hari kontak langsung dengan beberapa penumpang dalam melakukan pemeriksaan. Penyebab banyaknya karyawan terpapar dikarenakan masih ada pekerja di bandara dan penumpang serta pengunjung yang tidak mematuhi protokol kesehatan yaitu tidak menggunakan masker dengan baik dan benar serta masih adanya penumpang yang tidak melakukan pembatasan jarak. Kasus COVID-19 di Bandara International Kualanamu ditemukan pada pegawai di bulan Juni dan didapati 9 orang karyawan terpapar COVID-19. Sampai bulan Desember saat ini didapati ada 35 orang karyawan yang terpapar COVID-19. Tujuan dari penelitian ini adalah untuk mengetahui penerapan protokol kesehatan masa new normal di Bandara Internasional Kualanamu. Penelitian ini bersifat deskriptif dengan menggunakan metode penelitian kualitatif yang dilakukan di Bandara Internasional Kualanamu dengan menggunakan metode wawancara mendalam terhadap 4 orang Petugas AVSEC, 3 orang Pihak Maskapai, 5 orang Penumpang, 2 orang Petugas Kesehatan, dan 2 orang Pengelola Restaurant. Dari hasil penelitian yang telah dilakukan dapat diketahui bahwa penerapan protokol kesehatan COVID-19 masa new normal di Bandara Internasional Kualanamu sesuai dengan aturan yang telah ditetapkan oleh pemerintah. Penerapan protokol kesehatan ditemukan beberapa hambatan dan penyebab tidak dipatuhinya protokol kesehatan, dikarenakan ada beberapa penumpang dan pengunjung yang lalai dalam penerapan protokol kesehatan tidak memakai masker dengan baik dan benar seperti menurunkan masker pada area mulut atau dagu serta penumpang yang tidak melakukan pembatasan jarak terutama pada saat check-in, memvalidasi hasil rapid/swab test serta pada saat akan naik atau turun dari pesawat. Untuk itu Petugas Bandara Internasional Kualanamu diharapkan dapat terus menyampaikan pentingnya penerapan protokol kesehatan COVID-19 masa new normal. Penumpang juga diharapkan untuk lebih meningkatkan disiplin dalam menerapkan protokol kesehatan COVID-19.